El sistema de control interno y su incidencia en la gestión administrativa del colegio fiscal técnico agropecuario José Rodriguez Labandera, cantón Quevedo, periodo 2012 - Linares Miguez, Mariela Alexandra (2013)
This research project was conducted in the "Colegio Fiscal Técnico Agropecuario José Rodríguez Labandera " which is an educational institution established in the city of Quevedo, the aim of the research lies in an evaluation system of internal controls to campus for the development of the research methods used as the survey, testing the hypotheses, analyzing the causes and effects of the problem, in which it was determined that the Colegio José Rodríguez Labandera not have an adequate system of internal controls, and it was found that lack of tools and manual functions and administrative procedures, which has made the staff working in the institution are not clear about the activities to be performed, causing delays in managing and minimizing administrative efficiency and development effectiveness organizational. Considering these shortcomings in the system of internal controls, we conducted surveys to staff and faculty of the institution being able to obtain relevant information for the research and development and to make findings and recommendations based on the events that occurred at school. With all this can say that it met the objectives in this research project, suggesting recommendations to improve controls in administrative processes.